Pécs agrárrendszere a dualizmus korszakában = Agricultural system of Pécs under the dual monarchy - Kaposi, Zoltán (Közép-Európai Közlemények, 2018)
Pécs was the largest industrial and trade centre of the Southern Transdanubia region in the 19th century; in addition, it had significant agricultural capacities. The area of the city was about 6900 hectares. Most of the lands were used for agricultural purposes. From the aspect of ownership the some acre smallholdings were the most important. As a result of the high soil quality versatile agricultural production was possible (crop cultivation, livestock, horticulture etc…). The viticulture and winemaking stood out of the other agricultural production systems, these were practiced on 1438 hectares. Though the city went through quick industrialisation agriculture remained a dominant sector in employment and income generation. From the end of the 1880s agriculture was losing its significance due to the declining agricultural commodity prices and the phylloxera plague; however, it remained an important source of additional income for the local citizens. The agricultural products of Pécs were on the quickly growing local markets, but the wine and fruits played a significant role in the supply of far regions (for example Austria).